Hamstring Injuries: A Paradigm for Return to Play - Hoy, Michael K.; Stache, Stephen, Jr.; Roedl, Johannes B. (Seminars in Musculoskeletal Radiology, 2024)
Muscle injuries are the most common sports-related injuries, with hamstring involvement most common in professional athletes. These injuries can lead to significant time lost from play and have a high risk of reinjury. We review the anatomy, mechanisms of injury, diagnostic imaging modalities, and treatment techniques for hamstring injuries. We also present the latest evidence related to return to play (RTP) after hamstring injuries, including a review of articles targeted to RTP in European soccer (Union of European Football Associations), American football (National Football League), and other professional sports. Review of imaging findings in hamstring injury, grading systems for injuries, considerations for RTP, as well as advances in injury prevention, are discussed.
Keywords: return to play; hamstring strain; injuries; soccer; football